ISLAMIC SHARECROPPING PRACTICES: EVIDENCE FROM INDONESIAN LOCAL COMMUNITIES - Arif, Hermita; Purisamya, Asharin Juwita; Ali, Mohammad Mahbubi (Kesatuan Press, 2025)
Agricultural sharecropping partnerships in Indonesia face transparency and fair profit distribution challenges between landowners and farmers, often leading to disputes and inequitable outcomes. This phenomenon is particularly evident in South Sulawesi, where traditional farming practices intersect with Islamic principles. This research aims to explore the practice of sharecropping contracts between land owners and farmers and to investigate its adherence to Islamic principles. This study employs a descriptive qualitative method using thematic analysis to explain the partnership model practiced by local farmers in South Sulawesi and comparative analysis to assess its adherence to the Islamic principle of al-maharajah. Financial analysis is also applied to evaluate the sharecropping scheme's economic viability. The study results found that implementing a sharecropping partnership is economically beneficial to society in increasing income. The sharecropping partnership application follows the local culture inherited decades ago. The output sharing ratio applied is 1:2 or 50:50 depending on which party bears the production costs other than land, complying with the Islamic principle of profit and loss sharing. Preparing the financial record to increase trust from landowners and evaluate the sharing ratio scheme effectively is suggested.